Pengaruh Penerapan Sistem Informasi Akuntansi, Pemanfaatan Teknologi Informasi, Pengendalian Internal terhadap Kualitas Laporan Keuangan pada Bahruny Group - Rudy Fachruddin; Ferdiansyah Putra; Mulia Saputra; Sayuthi, Sayuthi (Al-Buhuts, 2024)
The study's objective is to comprehend and assess the quality of Bahruny Group's financial reports in light of their use of accounting information systems, IT, and internal control. This exam focuses on quantitative research. The participants in this study are 31 Bahruny Group employees. In this study, 31 people are used as respondents because the census method is used as a sampling method. Survey dispersion is the technique utilized in this review to gather information. The survey method is the name of this method. The data were analyzed using multiple linear analysis with the SPSS program. The study's findings indicate that the quality of the presented financial statements is influenced by the utilization of information technology, internal control, and accounting information systems. The remaining 14.3% is explained or explained by other variables that were not examined in this study, as evidenced by the R Square value of 0.857, which shows 0.857 (85.7%).